Business Strategy Formulation for Internet Service Provider (ISP): A Case Study of Iconnet by PT PLN Icon Plus - Pramudhito, Ari; Tricahyono, Dodie (International Journal of Science, Technology & Management, 2025)
Iconnet is a flagship product of Icon Plus designed to generate revenue in a new business line outside the electricity sector with the Beyond kWh concept, through the optimization of the strategic asset of Right of Way (ROW), which includes over 1.5 million electricity poles across Indonesia. This research aims to provide recommendations for developing Iconnet's strategy formulation using a qualitative approach, with data collection through in-depth interviews with three internal company sources and one external source. The analysis involves examining internal and external factors of the company using Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS), which are then combined into a Strategic Factor Analysis Summary (SFAS), followed by SWOT analysis, and evaluation of alternative strategies using the Quantitative Strategic Planning Matrix (QSPM). The results suggest enhancing human resources (HR) quality to improve product quality and customer satisfaction, increasing customer engagement to strengthen customer relationships, and expanding market targets based on a comprehensive customer database analysis. Iconnet formulates a three-year action plan focusing on three main aspects. First, in internal organization, performance evaluation using an analytics dashboard, along with HR competency mapping using AI and digital training programs. Second, in customer interaction, developing personalized service apps, digital marketing, and an integrated customer experience. Third, in supplier interaction, digitizing contracts and vendor evaluation through ERP systems, and collaborating with leading technology suppliers to enhance network and technological innovation.